Benefits and challenges: Qualitative exploration of women’s experiences during the COVID-19 pandemic in Fiji - Eunice Okyere; Kissinger Marfoh; Ditoga Kabukeinamala; Ramneek Goundar; Litia Makutu; Latileta Odrovakavula; Sovaia Vasukinatavea (PLoS ONE, 2025)
The COVID-19 pandemic and its preventive strategies resulted in changes in economic, social and health activities globally, but the effects of these changes on women, have not been systematically studied and documented in Fiji. The current study explored the experiences of women during the COVID-19 pandemic in Fiji, using a qualitative approach with a descriptive phenomenological design. A total of 110 women were purposively selected across various age groups, ethnicity, religion and different settings to improve the study area diversity. In-depth interviews were conducted using a semi-structured interview guide, and analyzed inductively, using the thematic approach. The three themes that emerged were employment and financial issues, health challenges during the COVID-19 pandemic and COVID-19 social and health benefits. The employment and financial issues identified included fear of losing job, difficulty finding a new job, job renewal challenges, decline in private businesses and high cost of living. Participants experienced health challenges including overweight and obesity, fear and anxiety, depression, insomnia and feeling helpless and worsened pre-existing health conditions. The COVID-19 social and health benefits included high sense of responsibility towards extended families, strengthened core family relationships, work-life balance, improvement in health status, healthy lifestyle behavior, and self-care awareness. The findings indicate the need for employers to address the employment and financial needs of women during emergency situations, like the COVID-19 pandemic. Health care managers, health care workers and policy makers should implement strategies to address the COVID-19 health challenges and strengthen the COVID-19 social and health benefits to improve the health of women, in the study area.